2001
DOI: 10.1086/321684
|View full text |Cite
|
Sign up to set email alerts
|

The Infrared Continuum Spectrum of VY Canis Majoris

Abstract: 3 Based on observations with ISO, an ESA project with instruments funded by ESA Member States (especially the PI countries: France, Germany, the Netherlands and the United Kingdom) with the participation of ISAS and NASA. ABSTRACTWe combine spectra of VY CMa obtained with the short-and long-wavelength spectrometers, SWS and LWS, on the Infrared Space Observatory to provide a first detailed continuum spectrum of this highly luminous star. The circumstellar dust cloud through which the star is observed is partia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 33 publications
(63 reference statements)
3
43
0
Order By: Relevance
“…The presence of metallic Fe in the CSE of VY CMa was postulated by Harwit et al (2001) and is also used to explain the SEDs of OH/IR stars (Kemper et al 2002). Moreover, metallic Fe is a product of the O-rich condensation sequence.…”
Section: A Continuum Opacity Sourcementioning
confidence: 88%
See 1 more Smart Citation
“…The presence of metallic Fe in the CSE of VY CMa was postulated by Harwit et al (2001) and is also used to explain the SEDs of OH/IR stars (Kemper et al 2002). Moreover, metallic Fe is a product of the O-rich condensation sequence.…”
Section: A Continuum Opacity Sourcementioning
confidence: 88%
“…VY CMa is an RSG experiencing extreme mass loss, which produces an optically thick circumstellar environment (CSE). The detailed analysis required to derive reliable dust-composition parameters for VY CMa is beyond the scope of this paper, and we refer to Harwit et al (2001) for a study of its ISO-SWS spectrum.…”
Section: The Samplementioning
confidence: 99%
“…Therefore the origin of the radio continuum is certainly not entirely photospheric. Indeed, models of the spectral energy distribution of VY CMa (e.g., Harwit et al 2001) suggest that at the observed frequencies the total flux is almost entirely reprocessed dust radiation, with the direct photospheric flux constituting of only a few percent of the total emission. Our measured flux of 0.6 Jy at 320 GHz is consistent with those models.…”
Section: Localization and Abundances Of The Tio And Tio 2 Gasmentioning
confidence: 99%
“…A proper identification of the type of silicates would also require the observation of the 18 μm band. The flux ratio F ν,E /F ν,W ∼ 0.4 (instead of unity) at the "continuum" wavelengths of 8.5 and 13 μm indicates achromatic attenuation, which is most likely due to metallic Fe, a crucial ingredient in the SED modelling of OH/IR stars and obscured RSG (Kemper et al 2002;Harwit et al 2001). The observed absorption towards 8 μm can be attributed to amorphous silicates, but only through scattering by fairly large grains.…”
Section: The Spectramentioning
confidence: 99%